Intercomparison of surface energy flux measurement systems used during the HiWATER‐MUSOEXE. Issue 23 (13th December 2013) - Xu, Ziwei; Liu, Shaomin; Li, Xin; Shi, Shengjin; Wang, Jiemin; Zhu, Zhongli; Xu, Tongren; Wang, Weizhen; Ma, Mingguo
Abstract [1] Agreement among instruments is very important for the Multi‐Scale Observation Experiment on Evapotranspiration over heterogeneous land surfaces of The Heihe Watershed Allied Telemetry Experimental Research (HiWATER‐MUSOEXE), particularly in regard to radiation and turbulent flux measurements. Before HiWATER‐MUSOEXE was conducted, 20 eddy covariance (EC) system sets, 18 radiometer sets, and seven large aperture scintillometers (LASs) sets were intercompared over the Gobi desert between 14 and 24 May 2012. For radiometers, the four‐component radiation measurements exhibited good agreement—the average root‐mean‐square error (RMSE) and mean relative error (MRE) for the net radiation were 10.38 W m−2 and 1.24%, respectively. With regard to the EC systems, the best consistency for sensible heat fluxes was found among CSAT3 sonic anemometers and Li7500A/Li7500/EC150 combinations (average RMSE, 12.30 W m−2 and MRE, −1.36%), followed by Gill sonic anemometers and Li7500A/Li7500 combinations when a proper angle of attack correction method was applied (average RMSE, 16.75 W m−2 and MRE, −5.52%). The sensible heat flux measured using different LASs agreed well with high correlation coefficients—the average RMSE and MRE values were 10.26 W m−2 and 5.48% for boundary layer scintillometer (BLS) 900, 16.32 W m−2 and 10.47% for BLS450, and 14.38 W m−2 and −3.72% for ZZLAS, respectively. The EC and LAS measurements were compared and agreed well over homogeneous underlying surfaces, which also indicated that the EC and LAS measurements would be comparable in the follow‐up experiment. The intercomparison results can be used to determine instrument placement and are very helpful for subsequent data analysis.